PENGARUH STRATEGI PEMBELAJARAN TERHADAP KEMAMPUAN KOGNITIF DAN KREATIVITAS DALAM MENYELESAIKAN SOAL MATEMATIKA - MUH. BACHTIAR Bachtiar (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. The Influence of Learning Strategy Towards Cognitive Ability and Creativity in Solving Mathematics Problems (An Experiment Study on Students at SMPN in Bone District. The Study aims at examining the influence of learning strategy towards cognitive ability and students’ creativity in solving Mathematics problems. The population of the study was the entire SMPN in Bone district with A accreditation and students of grade VII at SMPN 1 Watampone and SMPN 2 Watampone with as many as 129 students were chosen. The samples of the study were 25 grade VII.B students at SMPN 1 Watampone and 25 grad VII.A students at SMPN 2 Watampone.The Study was an experiment research with factorial desin. Data were collected using test result instrument in a form on an essay. Data were analyzed by employing desriptive analysis and inferential analysis with SPSS 22.00 program.The result of the study revealed that students’ cognitive ability taught by employing mind map learning strategy at the experiment 1 was in high category. Students’ cognitive ability taught by employing expository learning strategy at the experiment 2 was in fair category. Students’ creativity in solving Mathematics problems taught by employing mind map learning strategy at the experiment 1 was in fair category on the aspects f fluency, flexibility, and originality; whereas, students’ creativity in solving Mathematics problems taught by employing expository learning strategy at experiment 2 was in fair category on the aspects of fluency, flexibility, and originality. The results indicated that there were differences between cognitive ability and creativity in solving Mathematics problems of students who were taught by employing mind map learning strategy and expository learning strategy.